2021
DOI: 10.3389/fonc.2021.593587
|View full text |Cite
|
Sign up to set email alerts
|

A Nomogram Combining a Four-Gene Biomarker and Clinical Factors for Predicting Survival of Melanoma

Abstract: BackgroundCurrently there is no effective prognostic indicator for melanoma, the deadliest skin cancer. Thus, we aimed to develop and validate a nomogram predictive model for predicting survival of melanoma.MethodsFour hundred forty-nine melanoma cases with RNA sequencing (RNA-seq) data from TCGA were randomly divided into the training set I (n = 224) and validation set I (n = 225), 210 melanoma cases with RNA-seq data from Lund cohort of Lund University (available in GSE65904) were used as an external test se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…TRIM34 expression in goblet cells plays an essential role in generating the inner mucus layer and preventing excessive colon inflammation and tumorigenesis [42]. However, four genes, i.e., HPDL, GRI-PAP1, GBP2, and TRIM34, have been reported to exhibit prognostic significance with respect to melanoma for the first time, while HAPLN3, CCL8, FCGR2A, and IFITM1 [43][44][45][46] have been reported to relate with the initiation and immune microenvironment of cutaneous melanoma. Thus, it is necessary to conduct further in vitro and in vivo investigations to examine the role of those 4 pivotal genes in melanoma and their precise mechanisms of action.…”
Section: Discussionmentioning
confidence: 99%
“…TRIM34 expression in goblet cells plays an essential role in generating the inner mucus layer and preventing excessive colon inflammation and tumorigenesis [42]. However, four genes, i.e., HPDL, GRI-PAP1, GBP2, and TRIM34, have been reported to exhibit prognostic significance with respect to melanoma for the first time, while HAPLN3, CCL8, FCGR2A, and IFITM1 [43][44][45][46] have been reported to relate with the initiation and immune microenvironment of cutaneous melanoma. Thus, it is necessary to conduct further in vitro and in vivo investigations to examine the role of those 4 pivotal genes in melanoma and their precise mechanisms of action.…”
Section: Discussionmentioning
confidence: 99%
“…Out of our gene set, HAPLN3 has already been integrated into other prediction models, two of which were concerning melanoma [ 35 , 36 ]. These studies have concluded that HAPLN3 is a potential signature that could be used in prognosis, risk assessment, and prediction of immunotherapy response in melanoma patients, especially in combination with specific clinical features.…”
Section: Discussionmentioning
confidence: 99%
“…The gene clec7a that encodes a glycoprotein with a distinct role in innate immunity regulation was up-regulated after CAP treatment 39 . While clec7a over-expression conferred a prior drug resistance in leukemic cells 40 , 41 and was prognostic of poor prostate cancer relapse-free survival 42 , it constituted as one member of the immune-related prognostic panel associated with favorable melanoma survival 43 whose mutation has been associated with immunodeficiency and the pathogenesis of retinoblastoma 44 .…”
Section: Discussionmentioning
confidence: 99%